2017
DOI: 10.1177/0300060516677929
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin III and D-dimer levels as indicators of disease severity in patients with hyperlipidaemic or biliary acute pancreatitis

Abstract: ObjectiveTo assess changes in anticoagulation and fibrinolytic systems between biliary and hyperlipidaemic acute pancreatitis (AP).MethodsPatients with biliary or hyperlipidaemic AP were enrolled. Demographic and clinical data were collected, and antithrombin III (ATIII), protein C, protein S, and D-dimer levels were investigated.ResultsA total of 45 patients with biliary AP and 50 patients with hyperlipidaemic AP were included (68 with mild AP and 27 with moderately-severe AP). ATIII and protein C levels in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 55 publications
(74 reference statements)
0
19
0
3
Order By: Relevance
“…Studies showing that the coagulation system is affected in AP have also shown that while thrombosis occurs with activation of the coagulant system, thrombosis breakdown increases with an increase in fibrinolytic activity [18, 19, 32]. In a study of 139 patients with pancreatitis, Maeda et al suggested that D-dimer, antithrombin III, fibrin/fibrinogen breakdown products, platelet number and TAT levels investigated at presentation were superior to CRP (CRP) in estimating the prognosis of the disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showing that the coagulation system is affected in AP have also shown that while thrombosis occurs with activation of the coagulant system, thrombosis breakdown increases with an increase in fibrinolytic activity [18, 19, 32]. In a study of 139 patients with pancreatitis, Maeda et al suggested that D-dimer, antithrombin III, fibrin/fibrinogen breakdown products, platelet number and TAT levels investigated at presentation were superior to CRP (CRP) in estimating the prognosis of the disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…23 Anti-thrombin III with the help of heparin and heparan sulphate binds to and inactivates factor X and thrombin. 24 Protein C binds to thrombinthrombomodulin complex and is activated to inactivate factors VIII and V. Protein S is required as a cofactor in this protein C mediated inhibition. 25 Thrombomodulin which is a product of endothelial cells, acting independently, binds to and removes thrombin from circulation.…”
Section: Coagulationmentioning
confidence: 99%
“…Approximately 20% -50% of idiopathic severe acute pancreatitis is caused by biliary stones, with a maximum up to 60% -80% [6]. The clinical examination of biliary microlithiasis is difficult, and it is easy to be misdiagnosed as idiopathic pancreatitis [7].…”
Section: Biliarymentioning
confidence: 99%